Chapters in the evolution of chromatography - Ettre, Leslie S. (Imperial College Press, 2008)
Chromatography, invented more than 100 years ago, is the most widely used separation technique in the world today. It has helped the birth of modern analytical instrumentation and continues to strongly influence the profiles of our chemical, biochemical and clinical laboratories. This book deals with the history of the invention and evolution of chromatography and of the various chromatographic techniques. After discussing the precursors, it elaborates on the activities of M.S. Tswett, the inventor of the technique, and of a few selected key pioneers. It then summarizes the evolution of the var.